Functional types of lexical bundles in reading texts of Malaysian University English Test: a corpus study - Christina Sook Beng, Ong; Yuen, Chee Keong (Penerbit UKM, 2015)
It is widely claimed that many university students were found to be unprepared for the reading demands placed upon them. To provide students with an understanding of the features of the discourses they may encounter, this study investigates lexical bundles (LBs) used in the reading passages of Malaysian University English Test (MUET), a compulsory entrance examination for tertiary education. More specifically it aims to compare and contrast the functional types of LBs found in arts and science-based reading passages. A specialised corpus of MUET test papers made up of only the reading passages categorised into two main traditional disciplines; arts and science was built using WordSmith Tools Version 5. The lists of LBs of the identified disciplines were generated using WordSmith Tools Version 5. The generated data was then analysed qualitatively based on Hyland’s (2008) Functional Taxonomy. Findings revealed that although the number of LBs in both disciplines shows significant difference, many similar LBs are found. Science-based passages employ more research-based LBs whereas arts-based texts employ more participant-oriented LBs. These findings seemed to confirm that the functions of LBs are specific to particular disciplines. Hence, explicit teaching of LBs should be considered in schools and two separate sets of MUET reading tests where the first comprises of texts adopted from the scientific and technological context while the other made up of texts from the social sciences should be designed to accommodate both arts and science stream pre-university students.